Pengaruh Workload Pressure, Skeptisme Profesional, dan Kompetensi Auditor terhadap Kemampuan Auditor dalam Mendeteksi Kecurangan (Fraud) dengan Redflags sebagai Pemoderasi - Adinda Putri Bilqisth; Luqman Hakim (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study aims to examine the effect of workload pressure, professional skepticism, and auditor competence on the auditor's ability to detect fraud (FRAUD) with red flags as a moderator. This type of research is quantitative, and the population in this study are auditors working at a Public Accounting Firm in South Jakarta. The sample of this study was determined by a convenience sampling technique. To determine the minimum sample size, the researcher used the Lemme Show formula so that the total sample was 97 samples. The data analysis technique used was Structural Equation Modeling (SEM) using the SmartPLS Version 4.0 program for data processing. The results of the study indicate that there is a significant effect of workload pressure on the auditor's ability to detect fraud. There is a significant effect of professional skepticism on the auditor's ability to detect fraud. There is a significant effect of auditor competence on the auditor's ability to detect fraud. Red flags do not moderate the effect of professional skepticism on the auditor's ability to detect fraud. Red flags moderate the effect of auditor competence on the auditor's ability to detect fraud.